2015
DOI: 10.5137/1019-5149.jtn.13655-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative visualization of cranial nerves in skull base tumor surgery using diffusion tensor imaging technology

Abstract: ABSTRACTdiffusion tensor imaging (DTI) technology (17), it is possible now to identify the major brain white matter fibers. However, it is still difficult to achieve imaging of the small fiber bundles such as CNs. A number of recent researches have attempted to identify CNs using high-resolution or high-density DTI in subjects with or without skull base lesions (7,20). The present study aimed to identify CNs in patients with skull base tumor using DTI technology with special parameters and analyze the technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 27 publications
0
34
0
1
Order By: Relevance
“…A maximum of 959 participants were included across all studies (ranging from 1 to 150 subjects per study), if multiple studies form a single institution did not include overlapping patient groups. Twenty-two studies focused on imaging the cranial nerves in relation to a posterior fossa tumor (Taoka et al, 2006; Chen et al, 2011; Gerganov et al, 2011; Roundy et al, 2012; Zhang et al, 2013, 2017; Choi et al, 2014; Ulrich et al, 2014; Wei et al, 2015, 2016; Yoshino et al, 2015a,b, 2016; Borkar et al, 2016; Hilly et al, 2016; Ma et al, 2016; Song et al, 2016; Behan et al, 2017; d'Almeida et al, 2017; Li et al, 2017; Zolal et al, 2017a,b), 16 studies imaged the trigeminal nerve in patients with trigeminal neuralgia (Herweh et al, 2007; Fujiwara et al, 2011; Leal et al, 2011; Lutz et al, 2011, 2016; Hodaie et al, 2012; Liu et al, 2013; Wilcox et al, 2013; DeSouza et al, 2014, 2015; Lummel et al, 2015; Chen, D. Q. et al, 2016; Chen, S. T. et al, 2016; Lin et al, 2016; Neetu et al, 2016; Hung et al, 2017) and the remaining 3 studies evaluated DTI and tractography of the cranial nerves in various other pathologies including the cochlear nerve in cases of unilateral deafness (Vos et al, 2015), and the trigeminal nerve in patients with herpetic keratouveitis (Rousseau et al, 2015) and short lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) (Coskun et al, 2017) (Tables 1–3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A maximum of 959 participants were included across all studies (ranging from 1 to 150 subjects per study), if multiple studies form a single institution did not include overlapping patient groups. Twenty-two studies focused on imaging the cranial nerves in relation to a posterior fossa tumor (Taoka et al, 2006; Chen et al, 2011; Gerganov et al, 2011; Roundy et al, 2012; Zhang et al, 2013, 2017; Choi et al, 2014; Ulrich et al, 2014; Wei et al, 2015, 2016; Yoshino et al, 2015a,b, 2016; Borkar et al, 2016; Hilly et al, 2016; Ma et al, 2016; Song et al, 2016; Behan et al, 2017; d'Almeida et al, 2017; Li et al, 2017; Zolal et al, 2017a,b), 16 studies imaged the trigeminal nerve in patients with trigeminal neuralgia (Herweh et al, 2007; Fujiwara et al, 2011; Leal et al, 2011; Lutz et al, 2011, 2016; Hodaie et al, 2012; Liu et al, 2013; Wilcox et al, 2013; DeSouza et al, 2014, 2015; Lummel et al, 2015; Chen, D. Q. et al, 2016; Chen, S. T. et al, 2016; Lin et al, 2016; Neetu et al, 2016; Hung et al, 2017) and the remaining 3 studies evaluated DTI and tractography of the cranial nerves in various other pathologies including the cochlear nerve in cases of unilateral deafness (Vos et al, 2015), and the trigeminal nerve in patients with herpetic keratouveitis (Rousseau et al, 2015) and short lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) (Coskun et al, 2017) (Tables 1–3).…”
Section: Resultsmentioning
confidence: 99%
“…All 22 studies involving patients with brain tumors focused on generating tractography of the surrounding cranial nerves. Eighteen of those (82%) involved patients with a vestibular schwannoma (Figure 3) but cranial nerve tractography was also assessed in patients with trigeminal schwannomas (Wei et al, 2016), meningiomas (Ma et al, 2016; Yoshino et al, 2016; Behan et al, 2017; d'Almeida et al, 2017; Zolal et al, 2017a), brainstem cavernomas (Ulrich et al, 2014) and other unspecified cerebellopontine angle tumors (Roundy et al, 2012). Given the functional importance of preserving the facial nerve during surgery, almost all tumor studies (21/22, 95%) included tractography of CN VII or the VII/VIII complex, but tractography of other cranial nerves within the posterior fossa has also been demonstrated including CN IV (Ma et al, 2016; Yoshino et al, 2016), CN V (Chen et al, 2011; Ulrich et al, 2014; Wei et al, 2016; Yoshino et al, 2016; Behan et al, 2017; Zolal et al, 2017a) and CN VI (Ulrich et al, 2014; Yoshino et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have reported use of diffusion tensor imaging (DTI), FIESTA, diffusion spectrum imaging (DSI), and 3D-fast spoiled gradient echo dual echo (3D-FSPGR) to reconstruct and determine the intracranial course of cranial nerves. 7,8,14,15 Similarly, Yang et al have reported the use of preoperative simulation by fusing images of CTA and FIESTA for determining the intracranial course of abducens nerve compressed by petroclival meningioma. 9 However, pre-operative simulation using fusion images to determine the feeding vessels in skull base meningioma has not been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported advan-tage of preoperative simulation using advanced neuroimaging modalities in precise determination of the intracranial course of the nerves even in large skull base tumors with distorted anatomy. [7][8][9] Here, we report a case of huge clinoid meningioma where preoperative simulation of the tumor with a combination of three-dimensional multidetector computed tomography (3D-MDCT), three dimensional digital subtraction angiography (3D-DSA) and 3T-fast imaging employing steady-state acquisition (FIESTA) proved to be a useful adjunct tool to determine the exact location of the feeding artery and to facilitate surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…Нейровизуализация лицевого нерва в клинической практике используется редко, а использование ее методов с целью прогноза восстановления функции лицевого нерва при НЛН не изучено. Интракраниальную часть лицевого нерва визуализируют с помощью трактографии в основном для преоперативной подготовки при операциях по удалению опухолей головного мозга [6]. Экстракраниальную часть можно хорошо визуализировать с помощью ультразвукового исследования -нейросонографии (НСГ).…”
unclassified